Pengaruh Kepuasan atas Kualitas Pelayanan dan Citra Merek terhadap Loyalitas Pelanggan Garuda Indonesia di Sumatera Barat - Abror -; Susi Evanita; Khairul Hidayat (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2012)
The aims of this research are to determine (a) the relationship between customer satisfaction to customer loyalty of Garuda Indonesia based on five dimensions of service quality, (b) the relationship between brand image to customer loyalty of Garuda Indonesia. This research is a causative research with 156 respondents of Garuda Indonesia Airways customer in West Sumatera. By using multiple regression analysis, this study found (1) customer satisfaction on the physical evidence has no significant impact on customer loyalty, (2) customer satisfaction on reliability has significant impact on customer loyalty (3) customer satisfaction on responsiveness has no significant impact on customer loyalty (4) customer satisfaction on assurance has significant impact on customer loyalty, (5) customer satisfaction on empathy has no significant impact on customer loyalty, and (6) customer loyalty is influenced by brand image significantly. Garuda Indonesia Airways must be focused on the strategy how to maintain customer satisfaction on reliability, assurance and brand image. However, Garuda also take a look for physical evidence, responsiveness and empathy.